Perancangan Prototype Pembangkit Listrik Tenaga Mikro Hidro Berbasis Turbin Crossflow Skala Laboratorium Menggunakan Metode VDI 2221 - Fajar Kartono; Joko Prihartono; Tan Rico Satria (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The energy that is stored in water can be used to generate electricity by taking advantage of the potential energy available, like the energy from waterfalls and the movement of flowing water. Micro-hydropower plants (PLTMH) are one solution to address the energy crisis, particularly in electricity. VDI 2221 is a method that German engineers use as a guideline when designing construction projects. The VDI (Verein Deutsher Ingeneure or German Engineers Association) design process involves several stages: task description, design concept determination, physical design, and detailed design. Based on the solution principle matrix table, 3 variants were obtained, each of which has criteria. Of the 3 variants that have been evaluated, variant 2 was obtained with results that met the requirements. The cost analysis table shows that the total cost for designing a prototype test equipment for a micro-hydroelectric power plant (PLTMH) based on a laboratory-scale crossflow turbine is Rp 10,032,000. This cost includes instrumentation, control and electrical panels, measuring instruments, pipe instruments, frame and casing, and unforeseen costs.